Relação entre testosterona, cognição e fragilidade em idosos - Alves, Claudia Adão (2018)
Studies show the relationship between testosterone, cognition and fragility in the context of old age. In a still small number and without conclusive results, this is a research theme that deserves deepening. The aim of this study was to analyze the relationship between testosterone levels, cognitive performance and fragility levels in men and women over 60 years. This is a quantitative study with comparative and correlational analyses. All ethical precepts governing research with human beings have been respected. The study was carried out with a convenience sample consisting of 190 participants, 76 men and 114 women, from three age groups (60-69; 70-79 and 80-89 years) enrolled in the Family Health Care center of a city in the interior of São Paulo state. Data were collected for sociodemographic characterization, cognitive performance, levels of fragility and dosage of hormones: TSH, Prolactin, Estradiol, Total testosterone and Free Testosterone Cal. There was Predominance of women, with a mean age of 70.68 (+ _ 6,07) years, married and with low schooling. With regard to cognition, 31.6% of men and 39.5% of women were below the cutoff score according to schooling in the MMME. In relation to fragility most were pre-Fragil. The change in TSH was 9.21% (n = 7) in men and 15.78% (n = 18) in females. The levels of prolactin men presented changes in relation to the age groups over 70 and 80 years but were not significant. The estradiol presented lower levels in long-lived women. The results of the relationship between total testosterone and cognition showed that for men over 80 years , there was a negative correlation of weak magnitude (r =-0.910 P = 0.00) for the domain temporal orientation and positive correlation of moderate Magnitude (r = 0,740 p = 0.03) for evocation memory. For women from 60 to 69 years, a positive correlation of weak magnitude (r = 0,307 p = 0.01) was observed for the attention and calculus domain. For women over 80 years old, a negative correlation of moderate magnitude (r =-0.691 p = 0.03) was found for the cognitive domain attention and calculus, and a positive correlation of moderate magnitude (r = 0,694 p = 0.03) for the language domain. Regarding the level of fragility, a positive correlation was found (r = 647 p = 0.05) of moderate magnitude for women over 80 years. In the analysis of correlation between calculated free testosterone and cognition data showed a positive correlation of moderate magnitude (r = 0,323 p = 0.05) for elderly men aged 60-69 years in the cognitive domain of memory and evocation. Among women in the age range from 60 to 69 years of age, there was a positive correlation of weak magnitude (r = 0,335 p = 0.01) for the cognitive domain of attention and calculus. These data provide contributions to the differences between gender and age group in the levels of testosterone, cognition and fragility of elderly people in the community.